Sedentary Plant-Parasitic Nematodes Alter Auxin Homeostasis via Multiple Strategies - Oosterbeek, Matthijs; Lozano-Torres, Jose L.; Bakker, Jaap; Goverse, Aska (Frontiers in Plant Science, 2021)
Sedentary endoparasites such as cyst and root-knot nematodes infect many important food crops and are major agro-economical pests worldwide. These plant-parasitic nematodes exploit endogenous molecular and physiological pathways in the roots of their host to establish unique feeding structures. These structures function as highly active transfer cells and metabolic sinks and are essential for the parasites’ growth and reproduction. Plant hormones like IAA are a fundamental component in the formation of these feeding complexes. However, their underlying molecular and biochemical mechanisms are still elusive despite recent advances in the field. This review presents a comprehensive overview of known functions of various auxins in plant-parasitic nematode infection sites, based on a systematic analysis of current literature. We evaluate multiple aspects involved in auxin homeostasis in plants, including anabolism, catabolism, transport, and signalling. From these analyses, a picture emerges that plant-parasitic nematodes have evolved multiple strategies to manipulate auxin homeostasis to establish a successful parasitic relationship with their host. Additionally, there appears to be a potential role for auxins other than IAA in plant-parasitic nematode infections that might be of interest to be further elucidated.